Three Approaches to Cooperative Learning in Higher Education - Kaufman, David; Sutow, Elliott; Dunn, Ken (Canadian Journal of Higher Education, 2017)
This paper first discusses cooperative learning and provides a rationale for its use in higher education. From the literature, six elements are identified that are considered essential to the success of cooperative learning: positive interdependence, face-to-face verbal interaction, individual accountability, social skills, group processing, and appropriate grouping. Three distinct approaches at the postsecondary level are described in the fields of Medicine, Dentistry and Mathematics, and feedback from faculty and students is reported. The three approaches are presented within the context of the disciplines and are compared across the disciplines with respect to the essential six elements. Finally, the authors share some lessons learned from their research and experience in order to assist faculty who wish to incorporate cooperative learning into their teaching.